Perkembangan Al Muktazilah dan Pengaruhnya di Dunia Islam - Nurfania, Andi Elvira; Santalia, Indo (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The history of the emergence of the Mu'tazilah sect emerged in the city of Basrah (Iraq) in the 2nd century Hijriyah, 105 – 110 AH, precisely during the reign of the caliph Abdul Malik Bin Marwan and the caliph Hisyam Bin Abdul Malik. The pioneer was a resident of Basrah, a former student of Al-Hasan Al-Bashri named Washil bin Atha? Al-Makhzumi Al-Ghozzal who was born in Medina in 700 AD, this appearance was because Wasil bin Atha? argued that Muslims are big sinners, not believers and not kafir which means he is wicked. there are several important figures of al muktazilah, namely wasil bin atha, abu huzzail al allaf, al jubai and others. As for the teachings of al muktazila, namely at tauhid, al adl, Al-Wa'ad wa al-Wa'id, Al-Manzilah bain Al-Manzilatain , Al Amr bi Al Ma'ruf wa Al Nahi an Al Munkar This Mu'tazilah sect influenced the development of the Islamic religion. Starting from a rational way of thinking that influenced the development of theology and philosophy Islam, to the point of inspiring many Muslim scholars.